The efficacy of quadruple therapy in non-ulcer Helicobacter Pylory gastritis in children: A prospective study - Hien Thi Phan; Ngoan Thi Dao; Phuong Minh Nguyen; Phu Huy Nguyen; Ha Thu Nguyen; Linh Thi Thuy Nguyen (Revista Cubana de Medicina Militar)
Aim: To compare the clinical improvement of two-regimen treatment using esomeprazole alone vs quadruple therapy in non-ulcer Helicobacter Pylori (H. pylori) gastritis in Vietnamese’s children.